(untitled) (Herald of Journalism, 2020)
Global changes in the media industry, forced rethink the principles of news journalism and adapt it to survive in the new media ecosystem. Search engines have an enormous impact on journalism, have expanded its tools to work with sources for information. Gradually, they also began to provide users news services began to do the traditional work of journal- ists. Today news aggregators are fighting for the media market, aggregators are serious competitors for the media. The article defines the role of search engines and aggregators in the transformation of the news industry, as- sesses their prospects as regulators of the content component of the com- munication space. The author concludes that expanding the monopoly of search engines only increases their social impact on users.